A Regional Health System Journey from Volume to Value: Roadmap to the Recognition as a 15 Top Health System in the USA for Quality Excellence - Harb NH; Said PA; Gusta SL; Wesson AM; Brautigam JD; Lemke JH; DeLessio ST; Cropper DP; Shammas NW (Dove Medical Press, 2022)
Nidal H Harb,1,2 Patricia A Said,1 Shirley L Gusta,1 Amanda M Wesson,1 Jordan D Brautigam,1 Jon H Lemke,1 Stephen T DeLessio,1 Douglas P Cropper,1 Nicolas W Shammas1,3 1Quality and Safety Department, Genesis Health System, Davenport, IA, USA; 2Cardiovascular Division, University of Iowa Hospitals and Clinics, Iowa City, IA, USA; 3Cardiology Research Unit, Midwest Cardiovascular Research Foundation, Davenport, IA, USACorrespondence: Nicolas W Shammas, Midwest Cardiovascular Research Foundation, 630 E 4th Street, Davenport, IA, 52801, USA, Tel +1 563-320-0263, Email shammas@mchsi.comAbstract: The 15 Top Health System program, an IBM Watson study, objectively measures health systems' performance overall on an annual basis using publicly reported data available from the Center for Medicare and Medicaid Services (CMS) and state data banks. Genesis Health System was recognized as an IBM Watson Health 15 Top Health System for two consecutive years in 2020 and 2021. A system-based approach with a "physician-lead, professionally-managed" framework, led to accomplishing the 15 Top Health System. The steps needed included adoption of the IBM Watson database to determine current status of certain key performance indicators, establishing a clinical effectiveness program and governance structure, and adopting Lean methodologies to analyze and determine appropriate interventions with long-term solution. The desire and willingness to accomplish this ambitious goal start with adoption by the Board and the administration of the health system while supplying appropriate financial and human resources that are dedicated to the success of the journey. In this manuscript, we describe the journey and steps implemented to accomplish the outcomes that led to the recognition as a 15 Top Health System for quality excellence.Keywords: 15 Top Health System, physician lead, clinical effectiveness, Lean methodology, Value of care